How to statistically model coherent MPI in optical communications? - Cancela, L. G.; Pires, J. O. (Signal Processing in Photonic Communications, SPPCom 2018, 2018)
The Beta distribution is used to model coherent MPI in optical communications and its fitness to describe experimental results is evaluated. It fits quite well to symmetric scenarios, but has some troubles when skewness matters.